Mineral bone density association with estrogen alpha receptor gene (ESRa) polymorphisms at postmenopausal osteoporosis - M Y Krylov; A. V. Grechenko; E Y Samarkina; N V Toroptsova; T A Korotkova; O A Nikitinskaya; V A Myakotkin; L I Benevolenskaya (Научно-практическая ревматология, 2005)
Objective. To study restrict fragment length polymorphisms (RFLP) Pvull and Xbal of estrogen gene (EG) receptor sites and its association with bone mineral density (BMD). Material and methods. 96 female with osteoporosis (OP) and 60 female without OP of comparable postmenopausal age (55-83 years) were included. Results. Statistically significant differences of Pvull genotypes frequencies prevalence between women with OP and control group so as absence of differences of Xbal genotypes frequencies prevalence were shown (p<0,05). Similar results were shown for combined genotypes PvuII/Xbal. Genotype ppxx in pts with OP was 3 times more frequent than in control group (29,2% and 10,0% respectively, p<0,05). Among pts with PP genotype mean spine BMD value came to 0,686±0,064 g/cm- and was significantly less (p<0,05) in comparison with Pp and pp genotypes (073310,073 g/cm 2 and 0,739±0,099 g/cm 2 respectively). Mean spine BMD value in pts with PPXx genotype was significantly less than in pts with ppxx genotype (0,66710,076 and 0,74410,102 g/cm2 respectively, p<0,05) and mean femoral neck BMD value in pts with the same genotype (PPXx) was significantly less than in pts with PpXx genotype (0,57710,079 and 0,62710,054 g/cm 2 respectively. Conclusion. We have confirmed that some EG genotypes and their combinations are associated with low spine and femoral neck BMD values in pts with OP.